Representation of logarithm of entire function in several complex variables - Brodyak, O.Ya.; Vasyl’kiv, Ya.V. (Carpathian Mathematical Publications, 2012)
The integral representation of some branch of an entire on $\mathbb{C}^n$ function which generalized the Poisson-Jensen-Stoll Formula is obtained.